Sensory recovery after infraorbital nerve avulsion injury - Lee, Sam Yong (Arch Craniofac Surg, 2020)
The infraorbital nerve is a branch of the trigeminal nerve. Injury to the infraorbital nerve can be caused by trauma, including various facial fractures. Due to this nerve injury, patients complain of numbness and pain in the entire cheek, the ala of nose, and upper lip. In general, spontaneous sensory recovery is expected after decompressive surgery. If nerve transection is confirmed, however, neurorrhaphy is typically performed. Here, we present a case in which microsurgery was not performed in a patient with Sunderland grade V avulsion injury of the infraorbital nerve due to a facial bone fracture. Gradual nerve function recovery was confirmed to be possible with conservative treatment and rehabilitation alone. These findings suggest that the nerve function recovery can be expected with conservative treatment, even for severe nerve injury for which microsurgery cannot be considered.